A Comparative Study on the Execution Time of Inheritance Distribution from the Perspectives of Islamic Law and Civil Law - Winni Angelia Eka Putri; Mairul Mairul (SEAN Institute, 2026)
Inheritance is a crucial aspect of family law, yet the prevalent socio-cultural practice of